2011
DOI: 10.1007/s10164-011-0319-4
|View full text |Cite
|
Sign up to set email alerts
|

Linking nest predation with brood parasitism in captive zebra finches: a multi-pair study

Abstract: Zebra finches (Taeniopygia guttata) are social, colonial nesting birds with moderate levels of intraspecific brood parasitism reported in both wild and captive populations. In a previous study, individually housed, captive zebra finch pairs responded to nest removal during the egglaying period by parasitising simulated active conspecific nests. In the study reported here, we investigated the role of nest loss as a proximate trigger for parasitism in a more naturalistic setting: small groups consisting of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Following experimental nest destruction, zebra finches showed no preference for laying a physiologically committed egg in a nest containing zebra finch eggs versus a nest containing Bengalese finch eggs. These results provide direct support for the Hamilton–Orians hypothesis in that nest destruction can cause facultative brood parasitism of both intraspecific (Feare ; McRae ; Shaw and Hauber , ) and interspecific nests (this study). Thus nest destruction could be an evolutionarily viable pathway toward obligate interspecific brood parasitism in birds.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Following experimental nest destruction, zebra finches showed no preference for laying a physiologically committed egg in a nest containing zebra finch eggs versus a nest containing Bengalese finch eggs. These results provide direct support for the Hamilton–Orians hypothesis in that nest destruction can cause facultative brood parasitism of both intraspecific (Feare ; McRae ; Shaw and Hauber , ) and interspecific nests (this study). Thus nest destruction could be an evolutionarily viable pathway toward obligate interspecific brood parasitism in birds.…”
Section: Discussionsupporting
confidence: 84%
“…For example, Hamilton and Orians () suggested that the laying of physiologically committed eggs in the nests of other birds following nest predation may be a viable pathway to the evolution of intraspecific and obligate interspecific brood parasitism (“Hamilton–Orians” hypothesis). This evolutionary hypothesis has strong support from theoretical modeling studies (Cichoń ; Robert and Sorci ) and has been demonstrated experimentally in an intraspecific parasitism context: captive zebra finches ( Taeniopygia guttata ) preferentially parasitized the active nests of conspecifics, as opposed to empty nests, following the removal of their own nest during the egg laying period (Shaw and Hauber , ). In the field, both starlings ( Sturnus vulgaris ) and moorhens ( Gallinula chloropus ) responded to the experimental removal of partially completed clutches by laying eggs in the active neighboring nests of conspecifics (Feare ; McRae ).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Specifically, obligate interspecific brood parasitism (OBP). Nevertheless, not all lineages that display these ecological traits are brood parasites, and some may have had parasitic strategies curtailed by successful host defenses, such as high levels of nest attention and nest defense (e.g., GonzalezMartin and Ruiz 1996;Geffen and Yom-Tov 2001;Shaw and Hauber 2012;Feeney et al 2012). Given the body of research describing evolutionary and ecological similarities between siblicidal and brood parasitic taxa, discussed below, we propose an evolutionary trajectory by which siblicide may be basal to brood parasitism.…”
Section: Introductionmentioning
confidence: 97%